PROPERTIES OF OXYGEN AND THEIR RELATIONSHIP TO EINSTEIN’S SPECIAL RELATIVITY THEORY: Received: 03rd June 2022; Revised: 06th July 2022, 12th July 2022, 15th July 2022; Accepted: 16th July 2022 - Low , Kin Onn; Khoo, Kee Tong; Koon, Ying Yao; Chua, Jia Xin (MATTER: International Journal of Science and Technology, 2022)
Oxygen has been shown able to be released from aqueous water when the water flows through magnetic fields. Such a production process is called magneto synthesis and it is successful when the principle of induced current took place. Oxygen produced from this newly discovered process possessed properties differently when compared to the photosynthesis process. This study can be made when the magneto synthesis process was carried out closed to the saturation point of oxygen dissolution equilibrium in aqueous water. At the saturation point, the exchange of oxygen atoms or molecules between these two processes has happened. This interchange state allowed a unique single steep-drop characteristic to be observed. The single steep-drop characteristic of the magneto synthesis process provides two pieces of evidence on the properties of oxygen; they are heavier by mass and higher by oxidative power. The unique properties as discovered are supported by Einstein’s Special Relativity Theory. In this matter, gamma-ray flashes are thought to produce when the hydrogen-electron pairs are formed. A mechanism where gamma-ray flashes could be produced was proposed and sufficient evidence for gamma-ray flashes to occur was outlined. The gamma-ray flashes are the clue in the inter-permutable between the mass and energy. This is the clue to let the special relativity theory take a place.